2019
DOI: 10.1177/1096348019861740
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Integrated Resort Experience on Customers’ Hedonic and Eudaimonic Well-Being

Abstract: This study examines the impact of integrated resort brand experiences (IRBEs) on customer well-being through the satisfaction of psychological needs. Partial least squares path modeling tests the hypotheses using a sample of 535 integrated resort customers. The results reveal that four dimensions of IRBE (i.e., sensory, affective, behavioral, and intellectual) have differing effects on needs satisfaction dimensions (i.e., autonomy, competence, and relatedness). Furthermore, the results show that autonomy and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 99 publications
3
25
0
Order By: Relevance
“…This can be true since consumers with a high need to belong often look to brands for meaning cues which may, in turn, help them to enhance their personal and social identification with brands (Gilal et al, 2020). These results support the findings of prior research which reported the strongest influence of relatedness needs satisfaction on consumer behavior outcomes such as wellbeing (Ahn, Back, & Boger, 2019), attachment with the human brand/celebrity (Thomson, 2006), attachment with a brand (Ahn & Back, 2019), and airline brand passion (Gilal et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This can be true since consumers with a high need to belong often look to brands for meaning cues which may, in turn, help them to enhance their personal and social identification with brands (Gilal et al, 2020). These results support the findings of prior research which reported the strongest influence of relatedness needs satisfaction on consumer behavior outcomes such as wellbeing (Ahn, Back, & Boger, 2019), attachment with the human brand/celebrity (Thomson, 2006), attachment with a brand (Ahn & Back, 2019), and airline brand passion (Gilal et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…BPNT posits that consumer behavior can be influenced by satisfying the basic needs of A‐C‐R. As such, researchers in the marketing realm has shown that marketing environment such as product design (Gilal et al, 2018), integrated resort experience (Ahn, Back, & Choe, 2019), positive word‐of‐mouth messages (Sweeney et al, 2014), and celebrity endorsers influence (Gilal et al, 2020) can significantly support customers’ A‐C‐R needs satisfaction. Consumer research has further shown that brands that managed to satisfying consumer basic needs for A‐C‐R can undoubtedly increase brand attachment (Thomson, 2006) and brand advocacy (Jillapalli & Wilcox, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a research model was developed to comprehensively explore the relationships between multiple tourism touch point-oriented experiences, well-being, and tourist behavior in China. In an attempt to bridge the research gaps in the tourism domain and follow the research in marketing (Ahn et al, 2019; Vada et al, 2019), the current study demonstrates the predictive power of multiple touch points during a tourism experience in both perceived well-being and tourist behavior intentions. Specifically, the developed conceptual framework explores the relationships between (1) four types of touch points in tourism experiences and perceived hedonic well-being; (2) four types of touch points in tourism experiences and perceived eudaimonic well-being; (3) hedonic well-being and tourist revisit intention; (4) hedonic well-being and tourist online word of mouth; (5) eudaimonic well-being and tourist revisit intention; and (6) eudaimonic well-being and tourist online word of mouth.…”
Section: Discussionmentioning
confidence: 86%
“…Compared to the dimensions of memorable tourism experiences (i.e., hedonism, novelty, local culture, refreshment, meaningfulness, involvement, and knowledge) (Kim et al, 2012; Tung & Ritchie, 2011), tourism experiences derived from destination-based touch points, partner-based touch points, tourist-based touch points, and social touch points were each measured by five items, which were mainly developed based on the definition of touch points proposed by Lemon and Verhoef (2016) as well as the scales of Wang (2015). Perceived hedonic well-being and eudaimonic well-being were each measured by four items, which were developed based on the studies by Ahn et al (2019), Diener (2009), and Vada et al (2019). Revisit intention and Online Word of Mouth were each measured using four items, which referred to the scales of Meng and Han (2018).…”
Section: Methodsmentioning
confidence: 99%
“…In a related vein, we believe that our work also highlights a broader need to investigate hospitality employee-related phenomena from a basic need satisfaction perspective. While there have been a growing number of hospitality customer-focused studies that have recently investigated basic need satisfaction in consumers (e.g., Ahn, Back, & Boger, 2019; Ahn, Back, & Choe, 2019; Lee, 2018), relatively few hospitality studies have focused on employee basic need satisfaction (e.g., Hu et al, 2019). Although a large body of research has investigated basic psychological need satisfaction in the mainstream management and psychology literatures, there remains a need to identify industry- and culture-based boundary conditions to the effects of basic psychological needs (Van den Broeck et al, 2016).…”
Section: Discussionmentioning
confidence: 99%